Persepsi Mahasiswa Dalam Merefleksikan Demokrasi Kepemimpinan Era Joko Widodo - Fadhilatul Amaliya; Anisa Fitriani Azizah; Dewi Sekar Pembayun; Anindya Rahma Fathiya; Tiara Jelita Andalusianti Roozan; Kuswan Hadji (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Perception or point of view is a thought about something that is aimed at trusting opinions in terms of thoughts and views. In general and globally regarding objects related to various angles of the problem. Of course there will be many schools and considerations, one of which is that in this decade, various thoughts and points of view have emerged from students. Of course, where there is feedback on the nation's leadership milestones cannot be separated from the role and participation of students in responding to leadership. One of them was in the Joko Widodo era. Therefore, with the issues that arise, of course students must be wise in responding to the existence of a democracy-based leadership model, where democracy is a representation of the proclamation of the Indonesian nation. Various levels of society should also take part in providing responses. In generating a response, of course it is not only negative and existing shortcomings, but also how to generate good, correct and wise perceptions. With the expected output in the future, students can allocate and reflect on various aspects that will later be able to improve the nation and state in a clear, firm and straightforward manner.